On designing multidimensional oil and gas business data structures for effective data warehousing and mining - Nimmagadda, Shastri; Dreher, Heinz (Institute of Electrical and Electronics Engineers (IEEE) Industrial Electronics Society, 2009)
Incomplete, improper and untimely information flow among operational units makes operations untidy and slow. Representing petroleum business data in multidimensional data structuring in a data warehousing environment is a solution for a manager?s strategic planning, and operationalmanagement. Conceptual multidimensional-relational (MR) and EMR (extended multidimensional-relationships) data mapping approaches are proposed for key exploration industry data management. These conceptual models facilitate in developing future implementation data models and help anexploration data analyst, for better understanding of data integration and effective data mining.